Efecto del abono orgánico biol en praderas naturales de la finca “La Ponderosa”, Marcabelí, El Oro. - Romero Freire., Paola Del Cisne (2024)
The present study assessed the impact of applying biol organic fertilizer on the botanical composition, biomass yield, and nutritional value of natural pastures on La Ponderosa farm, located in Marcabelí canton, El Oro province. An experimental design with completely randomized blocks was used, dividing 5000 m2 of the study area into control and biol treatment plots, with two phases (field and laboratory). The organic fertilizer was applied foliarly at a rate of 1 liter per 20-liter sprayer. The goal was to evaluate variables such as forage biomass, plant height, and nutritional composition. The results showed a significant change in botanical composition, with a predominance of Panicum maximum grass, a decrease in legumes, and weeds. Biomass increased significantly in the plots treated with biol fertilizer, rising from 0.99 kg to 5.06 kg, with a p-value of (0.023). A significant increase in plant height was also observed, with a p-value (<0.033), which is below the established range (<0.05), reaching an average of 159 cm in the treated plots compared to 61.66 cm in the control treatment. Regarding nutritional composition, significant differences were noted in moisture content (p-value 0.047), dry matter (p-value 0.047), and fat (p-value 0.046). Although no statistically significant results were detected for protein, ash, fiber, and non-nitrogenous elements, the data suggest a trend toward increased levels of these components in the forage treated with biol. Therefore, it is concluded that the application of biol in natural pastures increases biomass production and improves plant growth. While it does not have a significant effect on all analyzed nutritional composition parameters, it shows a tendency to enhance forage quality.